Low Level of CD4 Increases Risk of Cervical Intraepithelial Neoplasia in HIV-Infected Women: Kadar CD4 yang Rendah Meningkatkan Risiko Neoplasia Intraepitelial Serviks pada Perempuan yang Terinfeksi HIV - Mona Mariana; Ketut Suwiyoga; AAN Jaya Kusuma (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To study the risk of Cervical Intraepithelial Neoplasia (CIN) at higher CD4 levels compared to low CD4 levels in HIV-infected women. Method: Case-control study of 50 HIV-infected women who meet the inclusion and exclusion criteria and attended Kerti Praja Foundation outpatient clinic, Denpasar, who were then divided into 2 groups, those with CD4 500/mm3 and those with CD4 <500/mm3. Both groups had Pap smear examination done. The collected data was analyzed with Chi-Square test. Odds ratio was calculated to determine the influence of CD4 levels on the incidence of CIN in women infected with HIV. Result: In this study, three women were found to have CIN out of the 25 women with CD4 500/mm3 and nine women out of the 25 women with CD4 <500/mm3 were positive for CIN. The risk of CIN in HIV-infected women with low CD4 levels was 4.125 times higher than the risk in high levels of CD4 (95% CI = 1.96 - 17.7, p=0.047). Conclusion: The incidence of CIN in HIV-infected women is associated with the level of immunity, as characterized by levels of CD4. Decreased levels of CD4 in HIV-infected women may increase the risk for CIN incidence by four-fold. Keywords: CD4, cervical intraepithelial neoplasia, HIV